Analysis of Social Care Character Development in Islamic Religious Education Courses - Hapni Laila Siregar; Nurmayani Nurmayani (RIRAI Publisher, 2022)
The development of an increasingly modern era, on the one hand, progresses in various aspects of human life, but on the other hand also brings to the character and identity of the Indonesian nation, the waning of a sense of caring and social solidarity. Now egocentrism in the pattern of social relations in Indonesian society is increasingly visible, namely behavior that focuses on one's own welfare or gain at the expense of and at the expense of others. The development of social care characters must continue to be carried out, especially now that people's lives are increasingly difficult, the poverty gap is widening, and the crime rate is getting higher. Judging from the religious aspect, the attitude of social care will get 3 things, namely first, the road of sustenance becomes wide and open; second, being more sensitive to the life around us; third, get a reward. This study is a descriptive study to see the extent to which the development of social care characters in PAI courses. The data collection technique is using a questionnaire. The research was conducted in several departments at Medan State University in the even semester of the 2021-2022 Academic Year. This study resulted in the following findings: 1. the development of social care characters in PAI courses has only reached aspects of knowledge (cognitive) and attitudes (attitudes). This can be seen from the development of social care characters in both aspects which are already in the good category. 2. The development of social care characters from the behavioral aspect (behavior) in PAI courses is still in the poor category, for that it is necessary to design various social action tasks in the community that are carried out by students so that they will get a very meaningful experience.